Factors that affect quality of life in menopausal women - Ni Luh Nopi Andayani; I Wayan Adi Wira Guna (Physical Therapy Journal of Indonesia, 2023)
Background: The increase in life expectancy causes an increase in the number of women entering menopause, so this period negatively impacts a woman. Physiologically, at this time, women will decrease the function of the ovaries, which can affect a decrease in reproductive hormones. This situation will affect various health problems, which include physical and psychological changes, such as osteoporosis, diabetes, depression, and sleep problems; which these health problems will have an impact on the quality of life in menopausal women. Objective: This study aims to determine factors that affect the quality of life in menopausal women. Methods: This study uses a literature review method from secondary data in the form of research journals related to factors that affect the quality of life in menopausal women. Results: For a woman, changes in the quality of life are one of the effects of the menopause she is experiencing. These changes are influenced by several factors, namely physical activity (50%), education (33.3%), employment (16.7%), mild menopausal symptoms (16.7%), history of chronic disease (16.7%), and duration of menopause (16.7%). Conclusion: Based on some of the literature collected and the previous discussion, it can be concluded that several factors affect the quality of life, namely physical activity, education, occupation, mild menopausal symptoms, history of chronic disease, and duration of menopause.